2022
DOI: 10.3390/md20080536
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Research of Chitosan Chemical Modification Technologies and Their Applications

Abstract: Chitosan, which is derived from chitin, is the only known natural alkaline cationic polymer. Chitosan is a biological material that can significantly improve the living standard of the country. It has excellent properties such as good biodegradability, biocompatibility, and cell affinity, and has excellent biological activities such as antibacterial, antioxidant, and hemostasis. In recent years, the demand has increased significantly in many fields and has huge application potential. Due to the poor water solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(28 citation statements)
references
References 184 publications
0
28
0
Order By: Relevance
“…Chitosan oligosaccharide (COS) is derived by the hydrolysis and deacetylation of chitin, a polymer of N-acetyl-D-glucosamine, which is a main constituent of the exoskeleton of arthropods such as insects, crabs and shrimps, and the cell wall of fungi [ 15 , 16 , 17 , 18 , 19 ]. The physico-chemical and biological properties of this biopolymer have been explored in various fields including pharmaceuticals, biotechnology, textiles, cosmetics, biomedical engineering, agriculture, food processing, nutrition, water, and wastewater treatments [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan oligosaccharide (COS) is derived by the hydrolysis and deacetylation of chitin, a polymer of N-acetyl-D-glucosamine, which is a main constituent of the exoskeleton of arthropods such as insects, crabs and shrimps, and the cell wall of fungi [ 15 , 16 , 17 , 18 , 19 ]. The physico-chemical and biological properties of this biopolymer have been explored in various fields including pharmaceuticals, biotechnology, textiles, cosmetics, biomedical engineering, agriculture, food processing, nutrition, water, and wastewater treatments [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physico-chemical and biological properties of this biopolymer have been explored in various fields including pharmaceuticals, biotechnology, textiles, cosmetics, biomedical engineering, agriculture, food processing, nutrition, water, and wastewater treatments [ 20 , 21 , 22 , 23 ]. Due to its favorable pharmacokinetics and beneficial biological activities including anti-oxidative, anti-inflammatory, anti-diabetic, anti-bacterial, and anti-cancer activities, COS has the potential for development as dietary supplements or nutraceuticals [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Previously, we have reported that COS activated AMP-activated protein kinase (AMPK) in the intestinal epithelial cells via a mechanism involving calcium sensing receptor (CaSR)-mediated calcium release from the endoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 99%
“… Chemical structures of ( a ) fucoidan from F. vesiculosus showing alternating α (1→3) and α (1→4) linkages [ 14 ] and ( b ) chitosan showing (1→4) bonds [ 15 ]. …”
Section: Figurementioning
confidence: 99%
“…Sodium hydroxide (NaOH), the most common industrial alkali, has been widely used for extraction (e.g., d -glucans from edible mushrooms) and dissolution of polysaccharides (e.g., cellulose). − Moreover, alkali treatment will cause hydrolysis of hydrophobic acetyl groups and deprotonation of carboxylic acid groups, leading to an increased interaction between sugar chain molecules and water, which may also contribute to the enhancement of WL solubility. , Besides, the modification of water-soluble small or large molecules onto insoluble biopolymers can also improve their water solubility. For example, chemical modification methods of chitosan have been reviewed in many kinds of literature. , They indicate that chemical modification is a very necessary process to improve the water solubility of chitosan. For WL with acetyl and carboxylic groups, the relatively simple and potentially effective alkali treatment is worth trying first.…”
Section: Introductionmentioning
confidence: 99%
“…For example, chemical modification methods of chitosan have been reviewed in many kinds of literature. 16 , 17 They indicate that chemical modification is a very necessary process to improve the water solubility of chitosan. For WL with acetyl and carboxylic groups, the relatively simple and potentially effective alkali treatment is worth trying first.…”
Section: Introductionmentioning
confidence: 99%